2009
DOI: 10.1002/app.31065
|View full text |Cite
|
Sign up to set email alerts
|

New anionic surface‐active agent derived from wool proteins for hair treatment

Abstract: An anionic surface-active agent derived from wool proteins was developed as an alternative to the anionic surfactants extensively used in shampoo formulations. The physicochemical properties of this new surfaceactive agent prepared form wool proteins and its application for human hair treatments were studied. This new product could be considered a new mild anionic surfaceactive agent, as evidenced by the results found by the evaluation of its physicochemical properties. The new wool anionic surface-active agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…; Barba et al . 2010b, c). Contact angle measurements are affected by several factors, such as surface chemistry heterogeneity, roughness, surface deformability, surface configuration changes, surface polarity, and adsorption and desorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Barba et al . 2010b, c). Contact angle measurements are affected by several factors, such as surface chemistry heterogeneity, roughness, surface deformability, surface configuration changes, surface polarity, and adsorption and desorption.…”
Section: Resultsmentioning
confidence: 99%
“…Barba et al . (, 2010a, 2010b, 2010c) studied the beneficial effects of wool proteins and peptides on hand care and hair care ingredients. Lanzilotta et al .…”
Section: Introductionmentioning
confidence: 99%
“…and the interaction energy between the fi bre and the solution (Barba et al 2009). Because bleaching changes some of these factors (Zviak & Mill é quant 2005), the surface charge of hair fi bres following several rounds of bleaching is expected to be altered, thus explaining the differences in peptide interaction affi nity observed in the present study.…”
Section: Pdi-catalysed Peptide Binding To Over-bleached Hairmentioning
confidence: 99%
“…It is known that the strength and elasticity of hair decreases as a result of bleaching and permanent wave treatment [11,30,[34][35][36]. It has also been reported that the strength and elasticity of hair can be improved by treating with hydrolyzed proteins or peptides [20,[37][38][39][40].…”
Section: Effect Of Hydrolyzed Keratin On Permanent Wavingmentioning
confidence: 99%